A diversidade faunística nos livros didáticos do programa nacional para o 7° ano do ensino fundamental - Silva, Francisco Xavier da (2016)
The Brazil's biodiversity is one of the largest in the world, but textbooks rarely exploit and value the theme. This work took into account the relevance of teaching Fauna content in textbooks with the objective of verifying the content and its pedagogical and methodological aspects in the books that make up the Didactic Collections of Science of the National Textbook Program (PNLD - MEC 2014) indicated for the 7th year of elementary school, making a careful evaluation to understand the dimension of the problem and find viable suggestions to improve textbooks and teaching in Brazil. We used 10 of the 20 didactic collections of Natural Sciences made available by the MEC in 2014, for the 7th grade classes. The books were submitted to an analysis, taking as reference the PNLD, and prioritizing the theoretical content, visual resources and practical activities. As far as the research is concerned, it is a qualitative-quantitative and descriptive research. It was noted that:Onaverage, the books covered the topic in 44 pages (minimum of 24 and maximum of 62), between two and five chapters; As to theoretical content, five of the books made it difficult to contextualize (the comprehension of the reality lived by the student in the day to day); Some books presented improvements in the complementary resources, mainly associated with the arrival of the Internet in the schools, and they offered suggestions of consultations; 70% of the books evaluated did not present any type of suggestion of practical activities in relation to the fauna content; Only one book focused on the threats of extinction of the species of the fauna with greater consistency and showed projects of conservation; And the use of images of the exotic fauna was still frequent in the main examples. Thus, it is observed that the teaching of science in textbooks has been decontextualized, not considering reality, the absence of practical activities and the historical insistence on foreignism, especially in the images. This work had as Educational Product the creation of an application for cell phones and tablets with the endangered species of the Caatinga biome.